A practical guide to botulinum neurotoxin treatment of shoulder spasticity 1: Anatomy, physiology, and goal setting - Jacinto, Jorge; Camões-Barbosa, Alexandre; Carda, Stefano; Hoad, Damon; Wissel, Jörg (Frontiers in Neurology, 2022)
Botulinum neurotoxin type A (BoNT-A) is a first-line treatment option for post-stroke spasticity, reducing pain and involuntary movements and helping to restore function. BoNT-A is frequently injected into the arm, wrist, hand and/or finger muscles, but less often into the shoulder muscles, despite clinical trials demonstrating improvements in pain and function after shoulder BoNT-A injection. In part 1 of this two-part practical guide, we present an experts’ consensus on the use of BoNT-A injections in the multi-pattern treatment of shoulder spasticity to increase awareness of shoulder muscle injection with BoNT-A, alongside the more commonly injected upper limb muscles. Expert consensus was obtained from five European experts with a cumulative experience of more than 100 years of BoNT-A use in post-stroke spasticity. A patient-centred approach was proposed by the expert consensus: to identify which activities are limited by the spastic shoulder and consider treating the muscles that are involved in hindering those activities. Two patterns of shoulder spasticity were identified: for Pattern A (adduction, elevation, flexion and internal rotation of the shoulder), the expert panel recommended injecting the pectoralis major, teres major and subscapularis muscles; in most cases injecting only the pectoralis major and the teres major is sufficient for the first injection cycle; for Pattern B (abduction or adduction, extension and internal rotation of the shoulder), the panel recommended injecting the posterior part of the deltoid, the teres major and the latissimus dorsi in most cases. It is important to consider the local guidelines and product labels, as well as discussions within the multidisciplinary, multiprofessional team when deciding to inject shoulder muscles with BoNT-A. The choice of shoulder muscles for BoNT-A injection can be based on spastic pattern, but ideally should also firstly consider the functional limitation and patient expectations in order to establish better patient-centred treatment goals. These recommendations will be of benefit for clinicians who may not be experienced in evaluating and treating spastic shoulders.